Self Assessment System, Sistem Informasi Perpajakan, Penerapan E-Filing dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Dengan Kualitas Pelayanan Sebagai Variabel Intervening (Studi Empiris Pada KPP Pratama Karanganyar) - Daryono, Daryono (-)
The purpose of this study is to examine the influence of Self Assessment System, Tax Information System, Application of E-Filing and Tax Sanctions Against Taxpayer Compliance With Quality of Service as Intervening Variable (Empirical Study On KPP Pratama Karanganyar). This study is a census study. The data used are primary data by taking samples of the entire population of 100 (one hundred) respondents. This study uses analysis tools such as validity test, reliability test, linearity test, path analysis, multiple linear regression analysis, t test, F test and coefficient of determination.Testing the validity and reliability is done by using the technique one shot methods to get the results of all items declared valid and reliable. From the results of linearity test shows that the correct model is linear model. The result of t test of the first equation shows that the Self Assessment System, Tax Information System, and Tax Sanction have positive and significant impact on the Quality of Service. While for E-filing Application variable has positive and insignificant effect on Service Quality. From the second t-test showed that the Self Assessment System and the Application of E-Filing have a positive and significant effect on Taxpayer Compliance. While for the variable Tax Information System, Tax Sanctions and Service Quality have positive and insignificant effect on Taxpayer Compliance. F test results show that together independent variables affect Taxpayer Compliance. The result of calculation of direct influence and indirect influence of self assessment system, tax information system, e-filing application and taxation sanction to taxpayer compliance indicate that direct influence of self assessment system, tax information system, e-filing application and tax sanction to compulsory compliance Tax is the most effective and dominant rather than indirect influence. This means that both the self assessment system, the taxation information system, the application of e-filing and tax sanctions will further improve taxpayer compliance indirectly through the quality of service .. Recommendations submitted to management is that Effect Self Assessment System, Tax Information System, Application E- Filing and Tax Sanctions on taxpayer compliance is most effective and dominant than through the intervening variable Quality of Stewardship.Â Keywords: Self Assessment System, Tax Information System, Implementation of E-Filing, Tax Sanctions, Service Quality, Taxpayer Compliance.